TELAAH YURIDIS PENYELENGGARAAN TEKNOLOGI 5G DI INDONESIA: LANGKAH TRANSFORMASI MENUJU ERA SOCIETY 5.0 - Maudy Andreana Lestari; Ahmad M Ramli; Tasya Safiranita Ramli (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
In the era of society 5.0, technological developments live side by side with humans. Currently, 5G technology is present as the latest technology in the development of cellular telecommunications networks. Through the speed of data transmission offered, this technology can support other latest technologies to accompany human civilization to enter more significant progress. This is because there is no current technology that does not require high telecommunication networks, such as artificial intelligence, virtual reality, augmented reality, etc. Therefore, entering the progress of civilization that is increasingly significant requires a mature readiness for Indonesia in responding to technological developments. In the context of the law as a transformation infrastructure, the law must work side-by-side with technological developments. Because the direction and development of technology also require good regulation to run as it should. Thus, this research will use a normative juridical method with legal materials through analysis techniques in literature studies. It will produce education and recommendations regarding implementing 5G technology in Indonesia as a form of the author's juridical review of the applicable positive law